Economic questions of land usage – scarcity, sustainability - Magda, Róbert (Applied Studies in Agribusiness and Commerce, 2012)
The aim of this paper is to show the economic importance of land usage. This topic is important because land is the basis of industrial and agricultural production, as well as energy and environmental security. The focus of the analysis is the relationship between land usage and scarcity and sustainability.